Effects of Dimerization on the Structure and Biological Activity of Antimicrobial Peptide Ctx-Ha - Lorenzon, E. N. [UNESP]; Cespedes, G. F. [UNESP]; Vicente, E. F. [UNESP]; Nogueira, L. G. [UNESP]; Bauab, T. M. [UNESP]; Castro, M. S.; Cilli, Eduardo Maffud [UNESP] (Amer Soc Microbiology, 2012)
It is well known that cationic antimicrobial peptides (cAMPs) are potential microbicidal agents for the increasing problem of antimicrobial resistance. However, the physicochemical properties of each peptide need to be optimized for clinical use. To evaluate the effects of dimerization on the structure and biological activity of the antimicrobial peptide Ctx-Ha, we have synthesized the monomeric and three dimeric (Lys-branched) forms of the Ctx-Ha peptide by solid-phase peptide synthesis using a combination of 9-fluorenylmethyloxycarbonyl (Fmoc) and t-butoxycarbonyl (Boc) chemical approaches. The antimicrobial activity assay showed that dimerization decreases the ability of the peptide to inhibit growth of bacteria or fungi; however, the dimeric analogs displayed a higher level of bactericidal activity. In addition, a dramatic increase (50 times) in hemolytic activity was achieved with these analogs. Permeabilization studies showed that the rate of carboxyfluorescein release was higher for the dimeric peptides than for the monomeric peptide, especially in vesicles that contained sphingomyelin. Despite different biological activities, the secondary structure and pore diameter were not significantly altered by dimerization. In contrast to the case for other dimeric cAMPs, we have shown that dimerization selectively decreases the antimicrobial activity of this peptide and increases the hemolytic activity. The results also show that the interaction between dimeric peptides and the cell wall could be responsible for the decrease of the antimicrobial activity of these peptides.